ACT OF INFORMATION AND ELECTRONIC TRANSACTIONS IN SOCIOLOGY PERSPECTIVE - Agus Satory (Fakultas Hukum Universitas Djuanda Bogor, 2017)
The development of information and communication technology has also caused world relations to become borderless and cause significant social, economic and cultural change to take place so quickly. Such rapid advances in information technology have contributed greatly to the development of the world of information and electronic transactions. However, it can not be denied that such great progress on one side brings benefits to humanity, but on the other hand it can also bring harm to humanity. The provisions of Law Number 11 Year 2008 in conjunction with Law Number 19 Year 2016 on Information and Electronic Transactions in the perspective of sociology is due to the will to meet the legal needs of the community, including laws that reflect the cultural values of a nation (latency) . Where many events show that people demand different ways of interception and threats of defamation that are considered too heavy so that sanctions to the treatment of offenders is considered more severe than the actions done.